Climbing the Educational Mountain: A Metaphor for Real Culture Change for Indigenous Students in Remote Schools - Hewitson, Robyn (The Australian Journal of Indigenous Education, 2007)
Abstract The history of remote school education in the Northern Territory can best be summarised as years of lost opportunities, pedagogies of discrimination, and diminished lives for those parents and children who trusted and responded to the government’s invitation to come to school. From late 2001 to 2005 historic educational change occurred in the remote Community Education Centre of Kalkaringi and Daguragu in the Northern Territory, the site for the delivery of the Northern Territory’s first Year 12 Indigenous graduates studying in their own community school. At the heart of the historic achievement was a radical change in thinking about education for Indigenous students. This paper discusses some of the policy parameters and educational circumstances that prevented significant change in the delivery model of education for the Community Education Centres in addition to a conceptualisation of how that school circumvented the policy parameters and instituted real change from the ground up. The paper examines, through a critical lens, the nature of the culture change that was crafted and built upon within Kalkaringi School and its communities, despite an initial and significant sense of powerlessness felt by families and to some extent the teachers and principal within the school. Through the development and embrace of a metaphor of possibility and hope - the challenge of climbing the educational mountain formed the foundation for a dedicated and committed enactment of an equitable educational entitlement for remote Indigenous students.